On this foundation - Austin, Lynn N. (Austin, Lynn N. Restoration chronicles, 2015)
"Inspired by the biblical account of Nehemiah, Jewish cupbearer to the King of Persia, this story tells of the many dangers in his return to Jerusalem and the great opposition his people faced in their efforts to rebuild the city wall"--